The 2014-2020 budgetary period of Common Agricultural Policy (CAP) and its impact on Hungarian agricultural reform - Szabó, Péter (Agricultura (Maribor), 2014)
The new Common Agricultural Policy (CAP) has been designed to shrink funds that Hungarian agricultural reform will inevitably face over the period 2014-2020. Direct payments are to be decreased by 18 per cent, while rural development funds are expected to diminish by 13.5 per cent. Although the EU cake will grow less, the CAP will grow to a greater extent,and the agricultural and rural development piece of cake, providing support for Hungarian agricultural reform, will get bigger. A very encouraging fact is that young farmers will benefit the most since two new elements will come into force in this period of reform; land-based direct payments topped up by an additional 25 per cent and the sub-programme for young farmers enabling them a more favourable position within the system. The new plan period will be much more flexible than the previous one with several key elements becoming optional, which could protect Hungarian interests much better than was the case in the last period of agricultural policy reform (2006-2013).
Keywords: Common Agricultural Policy (CAP); skupna kmetijska politika (CAP); Hungarian agriculture; madžarsko kmetijstvo; policy reform instruments; inštrumenti reformske politike